2015
DOI: 10.1002/ajmg.b.32310
|View full text |Cite
|
Sign up to set email alerts
|

Causal discovery in an adult ADHD data set suggests indirect link between DAT1 genetic variants and striatal brain activation during reward processing

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a common and highly heritable disorder affecting both children and adults. One of the candidate genes for ADHD is DAT1, encoding the dopamine transporter. In an attempt to clarify its mode of action, we assessed brain activity during the reward anticipation phase of the Monetary Incentive Delay (MID) task in a functional MRI paradigm in 87 adult participants with ADHD and 77 controls (average age 36.5 years). The MID task activates the ventral striatum, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The selection of the appropriate data sets for the analysis was based on previous findings in our research and the availability of the data. An earlier paper [ 54 ] describes a causal analysis of data from the IMpACT study on a larger number of variables. Here we noticed, among other things, the causal link between inattention and hyperactivity/impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the appropriate data sets for the analysis was based on previous findings in our research and the availability of the data. An earlier paper [ 54 ] describes a causal analysis of data from the IMpACT study on a larger number of variables. Here we noticed, among other things, the causal link between inattention and hyperactivity/impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…Much focus has been devoted to identifying etiological factors underlying the disorder. Emerging genetic links to ADHD are promising [ 7 , 8 ] but require replication in diverse populations. Xu et al [ 9 ] have suggested that ADHD is associated with epigenetic aberrations among dopamine receptor and histone-modifying genes, suggesting possible influence of external causes, like secondhand smoke [ 10 , 11 ], on disorder etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our results are not directly comparable to these studies on smoking onset and cessation. Perhaps there is an interaction between the nine‐repeat allele and ADHD that yields this seemingly contradictory result (Sokolova et al, ) as ADHD was not studied in these studies evaluating smoking and DAT1. Or it is possible that the nine repeat polymorphisms may be linked to just one specific form of five identified nicotine dependence phenotypes (O'Loughlin et al, ).…”
Section: Discussionmentioning
confidence: 99%